Green supply chain management performance within the Thai hotel industry: A structural equation model - Pratyameteetham, Thapanaphat; Atthirawong, Walailak (My University, 2017)
This research used first and second order confirmatory factor analysis and structural equation modelling with AMOS 21 software to analyse green supply chain management (GSCM) performance within Thailand's 3-star, 4-star, and 5-star hotel industry. The final sample of 325 managers revealed that service users, suppliers, and green practices have a direct influence on the Thai hotel industry's GSCM performance. Further, it was found that the same drivers had an indirect impact on GSCM performance through service users. Also, competitors, laws, and environmental adherence have an indirect influence through suppliers. It was also determined that positive financial results can be obtained when hoteliers adjust their practices to conform to green supply chain concepts. Hoteliers should also establish networks of green hotels, while also implementing the 3Rs of reuse, reduce, and recycle. Hoteliers should also focus on using green energy, establishing green attitudes, and raising awareness amongst staff through green environment workshops.
Keywords: CFA; Drivers; Green practices; Green supply chain management; GSCM; Hotel industry; Structural equation modelling; Thailand